Education and entrepreneurship among women entrepreneurs in Uganda. A case study from the cities of Kampala and Wakiso - Olga Margret Maria Namasembe; Roser Manzanera-Ruiz (Revista Iberoamericana de Estudios de Desarrollo)
Studies on the interrelationship between women’s education, business and entrepreneurial motivations in sub-Saharan Africa are scarce. In this research, it is related women’s educational levels, initiatives, and motivations for entrepreneurship in Uganda. A qualitative approach was used. Hundred nine women entrepreneurs in the agricultural sector were interviewed. It concludes with the relationship between educational level, types of business and entrepreneurial motivations of Ugandan women to appreciate their diversity and differences. A better understanding of these can help policy makers and practitioners to assess whether their programmes are achieving their objectives and contribute to improved development efforts in this area.